2016
DOI: 10.1016/j.semcdb.2015.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fibroblast growth factors (FGFs): Mediators of energy homeostasis

Abstract: The metabolic fibroblast growth factors (FGFs), FGF1, FGF15/19, and FGF21 differ from classic FGFs in that they modulate energy homeostasis in response to fluctuating nutrient availability. These unique mediators of metabolism regulate a number of physiological processes which contribute to their potent pharmacological properties. Administration of pharmacological doses of these FGFs causes weight loss, increases energy expenditure, and improves carbohydrate and lipid metabolism in obese animal models. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 116 publications
1
68
0
Order By: Relevance
“…Importantly, hepatic overexpression of Pparγ2 and Mogat1 can drive liver steatosis even under a normal diet 27 41. While the influence of FGF15 on metabolic regulation in extrahepatic tissues ( eg, adipose tissue) is likely relevant for systemic lipid metabolism,39 42 we believe that the repressive effect of FGF15/19 on liver Pparγ2 expression may be relevant for the metabolic adaptation to fat intake. In support of this, we found that exogenous FGF15/19 administration inhibited hepatic Pparγ2 expression and function ( ie, Pparγ2 target genes expression) and that the expression of PPARγ2 was markedly induced in the liver of obese patients, who also show reduced FGF19 circulating levels 28 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Importantly, hepatic overexpression of Pparγ2 and Mogat1 can drive liver steatosis even under a normal diet 27 41. While the influence of FGF15 on metabolic regulation in extrahepatic tissues ( eg, adipose tissue) is likely relevant for systemic lipid metabolism,39 42 we believe that the repressive effect of FGF15/19 on liver Pparγ2 expression may be relevant for the metabolic adaptation to fat intake. In support of this, we found that exogenous FGF15/19 administration inhibited hepatic Pparγ2 expression and function ( ie, Pparγ2 target genes expression) and that the expression of PPARγ2 was markedly induced in the liver of obese patients, who also show reduced FGF19 circulating levels 28 .…”
Section: Discussionmentioning
confidence: 90%
“…In addition to its inhibitory effect on hepatic BA synthesis, FGF15/19 has been implicated in the regulation of energy homeostasis 8 9 39. It was early observed that FGF19 transgenic mice showed reduced fat content on a normal diet and were protected from diet-induced obesity 10.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast growth factor 21 (FGF21) is an endocrine hormone that regulates energy homeostasis (Markan and Potthoff, 2015). Single-nucleotide polymorphisms in the human FGF21 gene were recently associated with changes in macronutrient intake (i.e., the percentage of diet derived from carbohydrate, fat, or protein) (Chu et al, 2013; Tanaka et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These features make it a promising potential therapy for the treatment of type 2 diabetes [13]. Fgf21 is primarily expressed in the liver, white and brown adipose tissues, and the pancreas [4, 5].…”
Section: Introductionmentioning
confidence: 99%